2006
DOI: 10.1007/s00701-006-0817-2
|View full text |Cite
|
Sign up to set email alerts
|

A model for foramen ovale puncture training: Technical note

Abstract: This model for foramen ovale puncture training has demonstrated valuable help for initial practicing of this common neurosurgical procedure, particularly in centers where there are not many cadavers available for training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…However, different holes or channels can be accidentally entered at the base of the skull. Examples of these are the external mouth of the carotid canal, foramen lacerum, and jugulare foramen (Inamasu & Guiot, 2005;Almeida et al, 2006;Kaplan et al, 2007). These structures always have a potential for miscannulation.…”
Section: Discussionmentioning
confidence: 99%
“…However, different holes or channels can be accidentally entered at the base of the skull. Examples of these are the external mouth of the carotid canal, foramen lacerum, and jugulare foramen (Inamasu & Guiot, 2005;Almeida et al, 2006;Kaplan et al, 2007). These structures always have a potential for miscannulation.…”
Section: Discussionmentioning
confidence: 99%
“…[30][31][32][33][34][35][36] Such models contain colored blood vessels and dural sinuses, cranial nerves, brain, silicon structures that can also be used for bypasses, bone-like structures that can be drilled, and synthetic dura mater that can be sutured. CT/magnetic resonance imaging (MRI)-based 3D models produced using laser-sintered powdered polymers and 3D printers are also used for anatomy training and surgery simulation, [37][38][39][40][41][42] allowing for biomodeling of skull base and associated tumors and other lesions.…”
Section: ■ ■ Artificial Modelsmentioning
confidence: 99%
“…However, no LoE could be determined as trainees were not surveyed. A foramen ovale puncture model achieved a rating 1 content, as five experienced neurosurgeons concluded that it mimicked the human face and was sufficient for training neurosurgeons 15 . Again, no LoE was determined in this study.…”
Section: Introductionmentioning
confidence: 99%